1993
DOI: 10.1021/bi00211a012
|View full text |Cite
|
Sign up to set email alerts
|

Incision at DNA G.cntdot.T mispairs by extracts of mammalian cells occurs preferentially at cytosine methylation sites and is not targeted by a separate G.cntdot.T binding reaction

Abstract: We have investigated the specificities of G.T mismatch binding proteins and of G.T mismatch cleavage in extracts of mammalian cells. G.T mismatch-specific protein:DNA complex formation by cell extracts was independent of the local sequence context of the mismatch. Cell extracts performed similar levels of protein binding to DNA substrates in which a single G.T mispair was preceded by T, G, A, C, or 5-meC. In contrast, incision by extracts of the T-containing strand of a G.T mismatch exhibited a strong sequence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
22
0

Year Published

1994
1994
2008
2008

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 27 publications
3
22
0
Order By: Relevance
“…context of a CpG site regardless of its methylation status (34,(45)(46)(47), lacks an MBD domain altogether.…”
Section: ϫ6mentioning
confidence: 99%
“…context of a CpG site regardless of its methylation status (34,(45)(46)(47), lacks an MBD domain altogether.…”
Section: ϫ6mentioning
confidence: 99%
“…20,21 However, when sequence-context effects are taken into account, the preferred substrate for Tdg is a T·G mismatch in a methylated or unmethylated CpG dinucleotide. 19,[22][23][24] Methyl-CpG binding domain protein 4 (Mbd4) is another DNA glycosylase implicated in the suppression of CpG mutation. MBD4 can bind methylated CpG sites through its N-terminal methyl-binding domain and has been demonstrated to excise thymine residues from T·G mismatches.…”
Section: Introductionmentioning
confidence: 99%
“…Thus Day and co-workers (Sibghat-Ullah and Day, 1992) and Karran and colleagues (Griffin et al, 1994) showed that the enzyme present in crude extracts processed also 6-O-methylguanine/thymine mispairs by excising the thymine. The same workers also showed that the enzyme is sensitive to the sequence context of the mispair (Griffin and Karran, 1993;Day, 1993, 1995). Given the many capabilities of the enzyme in vitro, it is not easy to state with any certainty which, if any, of these enzymatic reactions reflect the true physiological function of the protein.…”
mentioning
confidence: 97%